2013
DOI: 10.1542/peds.2012-3650
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Care for Children With Developmental Disabilities

Abstract: Children with developmental disabilities often have unmet complex health care needs as well as significant physical and cognitive limitations. Children with more severe conditions and from low-income families are particularly at risk with high dental needs and poor access to care. In addition, children with developmental disabilities are living longer, requiring continued oral health care. This clinical report describes the effect that poor oral health has on children with developmental disabilities as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 13 publications
1
62
0
5
Order By: Relevance
“…The problem is gaining increasing recognition among health care professionals as the advances in medicine make it more likely for the affected children to survive into adulthood. In this respect, our observations entirely support the implications of recent reviews on oral health in handicapped children [4,16]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The problem is gaining increasing recognition among health care professionals as the advances in medicine make it more likely for the affected children to survive into adulthood. In this respect, our observations entirely support the implications of recent reviews on oral health in handicapped children [4,16]. …”
Section: Discussionsupporting
confidence: 88%
“…While it is recognized that patients with MPS have increased oral health needs [4,16], the degree to which these needs are met depends largely on socio-economic factors that differ across the countries. In this respect, it has recently been reported that the level of oral hygiene in patients with MPS in the UK was surprisingly similar to that in the general population [4].…”
Section: Introductionmentioning
confidence: 99%
“…People with mild or moderate intellectual and developmental disabilities (IDDs) 12 are generally at an increased risk of dental disease due to co-morbidities, dietary practices, behavioural challenges, and the potential need for extra attention in oral hygiene maintenance (e.g., tooth brushing); though these individuals can be treated successfully in the general practice setting, ED visits are not necessarily preventable for them, and therefore they were excluded from analysis. 13,14 Given the above, if the discharge summary included ICD codes related to dental trauma, oral soft tissues or developmental disability, those cases were excluded from the analysis.…”
Section: Data Aggregated At the Region Level (14 Local Health Integramentioning
confidence: 99%
“…Some CSHCN are at increased risk for dental disease through multiple mechanisms—exposure to medications high in sugar, the need for assistance in daily oral infection control (brushing/flossing), reduced ability to clear food from the mouth, reduced salivary function from the disorder or induced by medication, dietary preference for carbohydrates, the need for pureed food or a liquid diet, and oral care aversion (Norwood and Slayton 2013). Oral care aversion may motivate some caregivers to seek dental care for urgent needs, but forego routine preventive dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Policies to prevent dental problems in CASD/DD/MHC would not only help the children and their families, but would also help society by keeping the costs of needed health care lower, and keeping the burden on employment lower. Poor oral health has been associated with poor quality of life, and systemic illness (Norwood, and Slayton 2013). There is a significant need for all children to have their preventive dental care needs met and for caregivers to recognize and act upon those needs.…”
Section: Discussionmentioning
confidence: 99%